833 Using the GEMLR as a proxy for global health engagement of emergency care practitioners. Issue 3 (21st February 2022) - Jafar, Anisa; Prager, Gabrielle; Jones, Pete; Bromley, Claire; Kennedy, Harriet; Ndiaye, Haarith; Ingham, Jack
Abstract : Aims/Objectives/Background: There is broad involvement of emergency medicine (EM) practitioners in global EM (GEM) research. However this work is often siloed, reducing efficiency of collaboration and impeding healthy critical appraisal. The purpose of this novel longitudinal study is to identify the GEM research undertaken by those in EM. Quantifying, displaying and understanding the 'who', 'what' and 'where' of such research is a key step to facilitate collaboration and highlight important gaps to ultimately drive quality in GEM research as a whole. Methods/Design: The Global Emergency Medicine Literature Review (GEMLR) is an annual summary of the top-ranked GEM literature. A spreadsheet of all papers identified by each initial search (before ranking) is freely available. We searched the past six years of GEMLR's 3, 634 initial titles to identify authors with EM affiliations. We also collected data on author institutions, country focus, topic, funding sources and if co-authorship included local collaborators. Results/Conclusions: From 2014–2019 the GEMLR found over 800 individual papers with at least one EM affiliated author. Authors were from over 600 different institutions (see figure 1 ) and research focused on over 100 countries. Approximately 60% had no funding/documented and 5% papers did not include a local author. There are limitations, including the GEMLR search strategy and EM practitioners omitting their EM affiliations (a take home message, if we wish to strengthen EM's perceived research presence). However this study serves as a robust start-point to map GEM research engagement. Interestingly, the study demonstrates a modest UK author slice with 20 being identified, contributing to 12 papers over 6 years. Further analysis will target the sociodemographic association between the most/least researched countries, expanding to include further years of data. Using a data visualisation strategy we will make the work accessible online to provide leverage in areas of much-needed GEM research growth.